2021
DOI: 10.33715/inonusaglik.812385
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Health Literacy of the Nursing Students Studying at the First Aid and Emergency Department and the Effective Factors

Abstract: Çalışma, hemşirelik ile ilk ve acil yardım bölümü öğrencilerinin sağlık okuryazarlığı ve bu durumu etkileyen faktörleri tespit etmek amacıyla yapılmıştır. Çalışma, tanımlayıcı ve kesitsel tür araştırma dizaynında planlanmıştır. Veriler 21 Nisan-4 Mayıs 2020 tarihleri arasında toplanmıştır. Araştırmaya başlamadan önce etik kurul izni alınmıştır. Verilerin değerlendirilmesinde, ölçeğin normallik dağılımına bakılmış (Kolmogorov-Smirnov) ve non-parametrik testler uygulanmıştır. Tanımlayıcı istatistiksel metotlar (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
2
0
0
Order By: Relevance
“…We also found that as the income status of the students increased, the average health literacy score also increased, although, this was again not statistically significant. In the literature, there are studies showing no significant difference between income levels and health literacy levels, similar to our findings [26,27], although, it has been concluded that there is a positive relationship between income status and health literacy [25]. Individuals who perceive their own health positively also have higher health literacy scores [24,26,27].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We also found that as the income status of the students increased, the average health literacy score also increased, although, this was again not statistically significant. In the literature, there are studies showing no significant difference between income levels and health literacy levels, similar to our findings [26,27], although, it has been concluded that there is a positive relationship between income status and health literacy [25]. Individuals who perceive their own health positively also have higher health literacy scores [24,26,27].…”
Section: Discussionsupporting
confidence: 87%
“…In the literature, there are studies showing no significant difference between income levels and health literacy levels, similar to our findings [26,27], although, it has been concluded that there is a positive relationship between income status and health literacy [25]. Individuals who perceive their own health positively also have higher health literacy scores [24,26,27]. Based on the limited data in the literature, it can be said that there is a significant positive relationship between positive health perceptions and health literacy.…”
Section: Discussionsupporting
confidence: 85%